The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1016/j.jtbi.2015.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Bifurcations analysis of oscillating hypercycles

Abstract: We investigate the dynamics and transitions to extinction of hypercycles governed by periodic orbits. For a large enough number of hypercycle species (n > 4) the existence of a stable periodic orbit has been previously described, showing an apparent coincidence of the vanishing of the periodic orbit with the value of the replication quality factor Q where two unstable (non-zero) equilibrium points collide (named Q SS ). It has also been reported that, for values below Q SS , the system goes to extinction. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 14 publications
(33 citation statements)
references
References 24 publications
1
32
0
Order By: Relevance
“…Bifurcation analysis of oscillating hypercycles (n ! 4) has been reported recently [48]. A series of studies on small hypercycles n ¼ 2, 3, 4 revealed interesting dynamical phenomena such as delayed transitions and ghosts [49,50].…”
Section: ð4:1cþmentioning
confidence: 91%
“…Bifurcation analysis of oscillating hypercycles (n ! 4) has been reported recently [48]. A series of studies on small hypercycles n ¼ 2, 3, 4 revealed interesting dynamical phenomena such as delayed transitions and ghosts [49,50].…”
Section: ð4:1cþmentioning
confidence: 91%
“…where β = 1/2. This scaling law has been identified in physical systems (Strogatz & Westervelt 1989;Trickey & Virgin 1998), in metapopulation mathematical models for autocatalytic species (Sardanyés & Fontich 2010), in lowdimension (Sardanyés & Solé 2006;Sardanyés & Solé 2007) and high-dimensional replicator models exhibiting cooperation (Silvestre & Fontanari 2008;Guillamon et al 2015), as well as in single-species discrete models with Allee effects (Duarte et al 2012). If ghosts appear in green-desert transitions, the take home message is simple but leads to a grim picture: a given ecosystem might be on its way towards collapse despite the apparent stability.…”
Section: Introductionmentioning
confidence: 88%
“…More recently, Guillamon et al, [2015] investigated the periodic orbits in symmetric hypercycles with n = 5. In particular, they studied how these orbits behave in terms of Q using both numerical and analytical methods.…”
Section: Introductionmentioning
confidence: 99%
“…Under this scenario, the flows display transient periodic behavior since the trivial attractor is asymptotically globally stable. (B) Bifurcation curves of periodic orbits (red) and of fixed points (blue) taking coordinate x 4 (see [Guillamon et al, 2015] for details) with respect to parameter Q for the symmetric hypercycle, i.e., δ = 0, with A = 0.5 and k = 1. The parametric region in green allows for the coexistence of the hypercycle members in an oscillatory regime.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation